2022
DOI: 10.9734/jeai/2022/v44i930867
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Herbicides on Growth, Yield and Economics of Urdbean (Vigna mungo L.)

Abstract: A field experiment with the objectives to understand the effect of herbicides on weed infestation and blackgram yield involving herbicidal treatments (weedy check, hand weeding at 20 and 40 days after sowing, Pendimethalin 1000 g/ha (Pre-em), Imazethapyr 100 g/ha at 20 DAS, Fomesafen 250 g/ha at 20 DAS, Propaquizafop 100 g/ha at 20 DAS, Pendimethalin 1000 g/ha (Pre-em) fb Imazethapyr 100 g/ha at 20 DAS, Fomesafen 210 g/ha + propaquizafop 65 g/ha at 20 DAS was undertaken in RBD with three replications at Region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
2
1
0
1
Order By: Relevance
“…Although, in present study maximum grain and stover yields were recorded under the application of the highest dose of K-sap (10%) with 100% RDF followed by 10% G-sap with 100% RDF. This is in conformity with similar results obtained for Phaseolus aureus (Bai et al, 2008), Phaseolus radiata (Zodape et al, 2010;Pramanick et al, 2013) and Phaseolus mungo (Pramanick et al, 2016;Singh et al, 2022). Another studies suggested the yield increases in seaweedtreated plants might be associated with the presence of micro-elements and plant growth regulators, especially cytokinins in Kappaphycus and Gracilaria extracts that could be the reason for this yield enhancement (Featonby-Smith and Van Staden, 1983;Zhang and Ervin, 2008).…”
Section: Effect On Yield Attributes and Yields Of Maizesupporting
confidence: 88%
“…Although, in present study maximum grain and stover yields were recorded under the application of the highest dose of K-sap (10%) with 100% RDF followed by 10% G-sap with 100% RDF. This is in conformity with similar results obtained for Phaseolus aureus (Bai et al, 2008), Phaseolus radiata (Zodape et al, 2010;Pramanick et al, 2013) and Phaseolus mungo (Pramanick et al, 2016;Singh et al, 2022). Another studies suggested the yield increases in seaweedtreated plants might be associated with the presence of micro-elements and plant growth regulators, especially cytokinins in Kappaphycus and Gracilaria extracts that could be the reason for this yield enhancement (Featonby-Smith and Van Staden, 1983;Zhang and Ervin, 2008).…”
Section: Effect On Yield Attributes and Yields Of Maizesupporting
confidence: 88%
“…The stunting may be the outcome of decreased chlorophyll content due to virus infection [13] and also depends on time of infection and genotype. Similar results were also reported by Kolte [14], Nene [15], Singh [16]. Bashir et al [17] and Sharma et al [9] documented 8% as well as 23.8% reduction in plant height in ULCV infected T9 urdbean genotype respectively.…”
Section: Plant Heightsupporting
confidence: 87%
“…Hasilnya menunjukkan bahwa investor yang terorganisir, efisien dan tekun menyelidiki informasi pasar secara menyeluruh dan percaya bahwa pasar tidak pasti. Oleh karena itu, hal ini mengarahkan mereka ke sana untuk mengurangi bias keterwakilan (Singh et al, 2022).…”
Section: Pengaruh Representative Bias Terhadap Keputusan Investasi Me...unclassified